Delay Testing Method for Off-Site Asynchronous LTE Networks Based on Singular Value Removal - Shuangshuang Ni; Ke Cui; Kai Zhang; Guoxin Zheng (Journal of Computer Networks and Communications)
This paper presents an experimental campaign of transmission delay measurements under asynchronous condition for the communication-based train control (CBTC) systems. A three-stage asynchronous clock correction method is proposed. Before and after the working stage, the clock difference between transmitter and the receiver is calculated, moreover the relative offset and relative skew between two terminals of the working stage are derived, and it further leads towards the experimental verification of the transmission delay. In order to improve the measurement accuracy, the singular values are distinguished and eliminated in the test. Using this method, the transmission delay of the Long-Term Evolution for Metro (LTE-M) communication between the train and the signalling room in Shanghai Zhangjiang Metro Training Line is measured successfully, which demonstrates the effectiveness of the proposed one-way transmission delay test.